Um tempo para a literatura ou a vida entre o labirinto e a bússola - Martha-Toneto, Diana Junkes Bueno [UNESP] (My University, 2011)
Since the priors, man has been trying to understand the concept of time. From myth to quantum physics, time is something that inspires reflections on our own lives. Do we exist in time or for time? Literature, a peculiar form of knowledge, deals with the experience of time in many ways. By avoiding categorizations, literature converges time and space in a dimension in which labyrinth and compass converge: at the reading time, in the reader’s space, in the universe of the book, where Cronos, Kairos, and their heir, by excellence, the literary word, constellate. In this way, in this essay, I discuss some aspects of the relationship between literature and time, or still, what literature can teach us about the time.

O desejo de compreensão do tempo tem mobilizado os homens desde os primórdios. Dos mitos à física quântica, o tempo é algo que instiga a reflexão de nossa própria existência. Existimos no tempo ou para o tempo? A literatura, forma peculiar de conhecimento, lida com a experiência temporal de múltiplas maneiras e, ao evitar categorizações, faz convergir tempo e espaço em uma dimensão na qual o labirinto e a bússola aproximam-se: no tempo da leitura, no espaço do leitor, no universo da página, onde constelam Cronos, Kairos e sua herdeira por excelência, a palavra. O objetivo deste ensaio é refletir sobre as relações entre literatura e tempo ou, ainda, sobre o que a literatura tem a nos ensinar sobre o tempo.
Keywords: Literatura; Tempo; Linguagem poética; Literature; Time; Poetic language